Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi

Counts of southern elephant seals, Mirounga leonina, at Bouvet Island - Kirkman, S. P.; Hofmeyr, G. J. G.; Bester, M. N.; Isaksen, K. (Polar Biology, 2001)
Southern elephant seals were counted and classified into subjective sex-age classes on a weekly basis during expeditions to Bouvet Island in the austral summers of 1996/1997 and 1998/1999. The expeditions coincided with the moulting period of elephant seals aged one year and older. The presence of weaned pups at the principal haulout site, Nyrøysa/Westwindstranda, during the latter expedition, indicates that breeding took place here during 1998. Elephant seal counts from previous expeditions are summarised.
Keywords: Bouvetøya; NARE 1996/97; NARE 1998/99; marin biologi; pinnipedier; seler